Reformulasi Restitusi dalam Tindak Pidana Kekerasan Seksual Terhadap Korban Perempuan dengan Retardasi Mental - Zainur Ratna Savitri; Fanny Tanuwijaya; Yusuf Adiwibowo (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Article 7A paragraph (3) of Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims, states that "Submission of a request for restitution can be made before or after a court decision that has obtained permanent legal force through the LPSK". In formal juridical terms, these two articles give authority and at the same time legitimacy to the public prosecutor to include restitution in his demands, based on the recommendation of the LPSK so that it can be decided by the panel of judges examining the case. However, socially it turns out that the provisions of this article are not applicable, shown by the lack of openness for female victims with mental retardation to access protection from LPSK, either individually or through public prosecutors, so that the form of protection obtained by female victims with mental retardation is only limited to protection. abstract, there is no concrete and sustainable protection for victims. Therefore, an appropriate and specific system is needed for providing compensation to women with mental retardation who are victims of criminal acts of sexual violence, so that justice for women with mental retardation can be fulfilled